The effect of lifestyle intervention and depression symptoms on binge eating and relation of binge eating to gestational weight gain and child birth weight in the UPBEAT cohort of pregnant women living with obesity - Sam Burton; Francesca Solmi; Kathryn V. Dalrymple; Angela C. Flynn; Keith M. Godfrey; Lucilla Poston; Abigail Easter (PLoS ONE, 2025)
Binge eating is one of the most prevalent eating disorder behaviours in pregnancy, its risk factors and association with pregnancy-related outcomes has sparsely researched in this population. This study aimed to investigate: (hypothesis 1) the effectiveness of a lifestyle intervention in reducing binge eating; (hypothesis 2) the association between depressive symptoms and binge eating behaviours throughout the perinatal period; and (hypothesis 3) the association between binge eating, gestational weight gain and birthweight in a cohort of pregnant women with obesity. This is a planned secondary analysis of the UK Pregnancies Better Eating and Activity Trial (UPBEAT) randomized controlled trial. Exposures were trial arms (hypothesis 1); depressive symptoms (hypothesis 2); and number of weekly binge eating episodes and binge eating behaviours (hypothesis 3). Outcomes were number of weekly binge eating episodes and binge eating behaviours and cognitions (hypotheses 1 and 2), gestational weight gain and child’s birthweight (hypothesis 3). There was no evidence that the UPBEAT intervention was effective in reducing number of weekly binge eating behaviours (IRR .942; 95%CI .756, 1.174) or binge eating behaviours (IRR 1.005; 95%CI .861, 1.174). Increased levels of depressive symptoms were associated with a higher number of binge eating behaviours (IRR 1.031; 95%CI 1.015, 1.048) and its associated features (IRR 1.030; 95%CI 1.019, 1.041). There was evidence that more frequent binge eating behaviours lead to greater increase in gestational weight gain. (coefficient = .614; 95%CI .264, .964). There is a need for holistic interventions that promote maternal mental health and address binge eating behaviours. More work is required in the field to understand which interventions would prove efficacious.